Effect of Mirabegron to Reduce Lower Urinary Tract Symptoms in Prostatitis - Adeel Hyder Arain, Waqar Ahmed Memon, Javed Altaf Jat, Tamoor Jatoi, Ahsan Ali Arain, Pooran Mal (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To investigate effectiveness and safety of mirabegron in a patient’s symptoms associated with prostatitis in routine practice. Study Design: Prospective, pilot study Place and Duration of Study: Department of Urology, Liaquat University Hospital Jamshoro between 1st October 2020 and 30th November 2021 Methodology: Fifteen male subjects in two groups (control and treatment group with Mirabegron), 18 to 50 years old, with acute and chronic prostatitis according to the operational definition were recruited. The overactive bladder started with mirabegron at daily doses of 25mg, 50mg, and 100 mg respectively. Results: The mean ages were 47.7±2.1 years and 33.8±7.0 years respectively in the control and mirabegron groups. The significant efficacy in treating OAB symptoms such as frequent urination, urge incontinence, and urgency. For mirabegron 50 and 100 mg, the mean volume of urine passed per micturition was observed as early as the first assessment after 4-week’s duration and remained stable throughout treatment for up to 12 months. In terms of dry rates, our analyses revealed a considerable improvement with mirabegron 50mg and 100 mg. Patients considered their treatment with mirabegron to be worthwhile, according to an analysis of patient’s satisfaction treatment criteria. Mirabegron observed to be safe in OAB clinical trials with prostatitis that lasted up to 12 months. Conclusion: When contrasted with existing antimuscarinics that restricted due to associated adverse effects and insufficient effectiveness, mirabegron found improved compliance with balance between effectiveness and safety in Pakistani patients with associated symptoms in prostatitis. Key words: Prostatitis, Mirabegron, Effectiveness